Duregraph: Uma Abordagem Metodológica para Investigação Da Duração Na Imagem Fotográfica - Van Vliet, D; Mortensen Steagall, M (Universidade Estadual do Parana, 2021)
This article considers the methodological framework that was designed for a practice-led research project for a Master's degree in Design named Duregraph: A methodological approach to duration in the photographic image. Currently, there is a great appreciation of research methodologies in art and design capable of producing investigations that inform practice, where practice, knowledge and writing contextualize this epistemology. Duregraph is a neologism developed to express artistic considerations made through the photographic image for the investigation of a temporal reality that is detached from mathematical quantification. These images question duration and forms of representation to investigate the inversion of the power relations between image and its audience. The purpose of the article is to bring the light of scrutiny to the thinking used in the construction of the research as a way of questioning through practice.
Keywords: Photography; Post-Photographic; Practice-oriented research; Duration; Methodology